Use of FEM and DoE to reduce the forming force during cold extrusion of prismatic cell housings - Austen, Michael; Noneder, Johannes; Merklein, Marion (Key Engineering Materials, 2014)
These days, the call for more efficient cars, e.g. EURO 6, to reduce substantial the emissions of carbon dioxide and nitrous oxide raises the demand and development for Battery Electric Vehicles (BEV) or Plug-in Hybrid Electric Vehicles (PHEV). Thus, the German Government in cooperation with the industry has the goal to get at least 6 million electric vehicles on German streets by the year 2030. Until today battery systems increase the car's weight significantly, therefore weight reduction and utilization of the required space are two of the most important strategies. Because of its low density and high formability aluminum is preferred as cell housing material. Besides a light material it is necessary to use the required space of the battery pack in the car as efficient as possible. Thus a prismatic shape is favored compared to a cylindrical one. Unfortunately a prismatic cell causes an asymmetric material flow and an asymmetric tool loading during the production via bulk metal forming as the material tends to flow into the direction of the larger edges of the housing walls. That is why new forming tools for bulk forming have to be developed. To do this economically the development will be done by using design of experiments (DoE) and the finite element method (FEM). On the one hand DoE shortens time-consuming FE-simulations by stating exactly which simulations need to be done to identify main determining factors for the personal command variable(s) e.g. tool lifetime. On the other hand FEM can be used to achieve simulation results, e.g. tool loading, which are comparable to real life experiments. By using DoE, 2D FE-simulations show that the geometry of the punch's extrusion shoulder can decrease the required forming force precisely. In addition the geometry of so called deceleration seams can affect the forming force in minor degree. In combination of all significant geometric parameters and the number and position of deceleration seams the tool loading of a cold extrusion punch could be reduced significantly. © 2014 Trans Tech Publications, Switzerland.
LFT Import::2019-07-29 (2014)
Keywords: Bulk metal forming; Cold extrusion; DoE; FEM; Forming force; Prismatic cell housings; Simulation